A perfusion-independent high-throughput method to isolate liver sinusoidal endothelial cells - Babin-Ebell Gonçalves, Anna; Mao, Yifang; Baljkas, Tinja; Wiedmann, Felix Tobias; Eis, Larissa; Pilz, Franziska; Winkler, Manuel; Kürschner, Sina Wietje; Hoffarth, Marlene; Funaya, Charlotta; Shahidi, Réza; Géraud, Cyrill; et al. (Communications biology, 2025)
Liver sinusoidal endothelial cells (LSECs) critically regulate homeostatic liver function and liver pathogenesis. However, the isolation of LSECs remains a major technological bottleneck in studying molecular mechanisms governing LSEC functions. Current techniques to isolate LSECs, relying on perfusion-dependent liver digestion, are cumbersome with limited throughput. We here describe a perfusion-independent high-throughput procedure to isolate LSECs with high purity. Indifferently from previous perfusion-independent approaches, chopped liver tissue was incubated in the digestion mix for 30 minutes with intermittent mixing with a serological pipette. This led to the safeguarding of LSEC integrity and yielded 10 ± 1.0 million LSECs per adult mouse liver, which is far higher than previous perfusion-independent protocols and comparable yield to established perfusion-dependent protocols for isolating LSECs. Combining magnetic and fluorescence-activated cell sorting (FACS), LSECs from different zones of the hepatic sinusoid can now be isolated in high numbers in less than two hours for downstream applications including proteomics. Our protocol enables the isolation of LSECs from fibrotic liver tissues from mice and healthy liver tissues from higher vertebrate species (pigs), where traditional perfusion-based digestion protocols have very limited application. In conclusion, these technical advancements reduce post-mortem changes in the LSEC state and aid in reliable investigation of LSEC functions.
Gesehen am 27.03.2025